THE PRACTICAL WAYS FOR IMPROVING LISTENING COMPREHENSION IN ENGLISH - Ismoilov Sardorbek G’ayrat o‘g’li (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
This article deals with numerous reasonable and practical ways of boosting listening skills in the English language. Also, all suggested methods and solutions are based on reliable facts and details. They will be supported with solid reasons as well as examples.